Neonatal screening external quality assessment in China, 2014. (December 2015) - Zhong, Kun; Wang, Wei; He, Falin; Wang, Zhiguo
Objective: To analyze the 2014 results of neonatal screening external quality assessment (EQA) performed by the Chinese National Centre for Clinical Laboratories. Methods: EQA test panels consisting of five dried blood spots (three panels for phenylalanine (Phe) and thyroid stimulating hormone (TSH), two for glucose-6-phosphate dehydrogenase (G6PD) and 17-alpha-hydroxy progesterone (17-OHP)) were distributed to laboratories and the results collected and evaluated. To compare the correct recognition rates, chi-square test was used. Results: Test results were received from 170 laboratories for Phe, 176 for TSH, 65 for G6PD and 65 for 17-OHP. The total number of effective quantitative and qualitative results of Phe, TSH, G6PD and 17-OHP were 2520 and 2370, 2605 and 2450, 645 and 530, 645 and 645, respectively. The overall correct recognition rates for qualitative tests of Phe, TSH, G6PD and 17-OHP were 99.79 %, 99.67 %, 93.40 % and 99.84 %, and the proportion of acceptable quantitative results were 94.48 %, 98.31 %, 84.65 % and 99.84 %, respectively. There were significant differences in the rates of acceptable quantitative results of the two measurement systems for Phe, TSH and G6PD ( p <0.001); χ 2 test showed significant differences in correct recognition or acceptable rates among programmes ( p <0.001). Conclusion: Most of the quantitative results were acceptable and the overall correct recognition rates in qualitative results approached 100%. Distributing more challenging samples and increasing the range of concentrations of EQA samples will improve standards in future assessments.